Transcriptome analysis reveals the molecular regulatory network of muscle development and meat quality in Sunit lamb supplemented with dietary probiotic. (December 2022) - Zhang, Min; Guo, Yueying; Su, Rina; Corazzin, Mirco; Hou, Ran; Xie, Jingyu; Zhang, Yue; Zhao, Lihua; Su, Lin; Jin, Ye
Abstract: Supplementing animal feed with probiotic additives can promote muscle production and improve meat quality. The study aimed to explore the effects of dietary probiotics supplementation on the performance, meat quality and muscle transcriptome profile in Sunit lamb. Overall, feeding probiotics significantly increased the body length, LT area, pH24h and intramuscular fat (IMF) content, but decreased cooking loss and meat shear force compared to the control group ( P  < .05). A total of 651 differentially expressed genes (DEGs) were found in probiotic supplemented lambs. Pathway analysis revealed that DEGs were involved in multiple pathways related to muscle development and fat deposition, such as the ECM-receptor interactions, the MAPK signaling pathway and the FoxO signaling pathway. Therefore, dietary probiotic supplementation can improve muscle development and final meat quality in Sunit lambs by altering gene expression profiles associated with key pathways, providing unique insights into the molecular mechanisms by which dietary probiotics regulate muscle development in the lamb industry.